2018
DOI: 10.1101/276980
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Mean-Variance QTL Mapping on a Background of Variance Heterogeneity

Abstract: Most QTL mapping approaches seek to identify "mean QTL", genetic loci that influence the phenotype mean, after assuming that all individuals in the mapping population have equal residual variance. Recent work has broadened the scope of QTL mapping to identify genetic loci that influence phenotype variance, termed "variance QTL", or some combination of mean and variance, which we term "mean-variance QTL".Even these approaches, however, fail to address situations where some other factor, be it an environmental f… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
5
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
2
2

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 67 publications
2
5
0
Order By: Relevance
“…We observed no inflation in FPR for the Levene’s test under the null (i.e., no vQTL effect) regardless of the skewness or kurtosis of the phenotype distribution or the presence or absence of the SNP effect on mean (Supplementary Figure 1a). These findings are in line with the results from previous studies 16,20,30 that demonstrate the Levene’s test is robust to the distribution of phenotype. The FPR of the Bartlett’s test or DGLM was inflated if the phenotype distribution was skewed or heavy-tailed (Supplementary Figure 1a).…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…We observed no inflation in FPR for the Levene’s test under the null (i.e., no vQTL effect) regardless of the skewness or kurtosis of the phenotype distribution or the presence or absence of the SNP effect on mean (Supplementary Figure 1a). These findings are in line with the results from previous studies 16,20,30 that demonstrate the Levene’s test is robust to the distribution of phenotype. The FPR of the Bartlett’s test or DGLM was inflated if the phenotype distribution was skewed or heavy-tailed (Supplementary Figure 1a).…”
Section: Resultssupporting
confidence: 91%
“…We found that the FPR of the Levene’s test was well-calibrated across all simulation scenarios whereas the other methods showed an inflated FPR if the phenotype distribution was skewed or heavy-tailed under the null hypothesis (i.e., no vQTL effect), despite that the Levene’s test appeared to be less powerful than the other methods under the alternative hypothesis in particular when the per-variant vQTL effect was small (Figure 2 and Supplementary Figure 1). Parametric bootstrap or permutation procedures have been proposed to reduce the inflation in the test-statistics of DGLM and LRT-based method, both of which are expected to be more powerful than the Levene’s test 28,30 , but bootstrap and permutation are computationally inefficient and thus not practically applicable to biobank data such as the UKB. In addition, we observed inflated FPR for the Levene’s test in the absence of vQTL effects but in the presence of QTL effects if the phenotype was transformed by logarithm transformation or RINT.…”
Section: Discussionmentioning
confidence: 99%
“…In the case of genetic factors, they can be mapped, as illustrated in one companion article (Corty et al 2018). In the case of covariates, they can be accommodated, which can increase power and improve false positive rate control, as illustrated in another companion article (Corty and Valdar 2018).…”
Section: Resultsmentioning
confidence: 99%
“…To calculate the empirical, FWER-controlled p -value of each test at each locus we advocate use of a permutation procedure (Corty and Valdar 2018). Like previous work on permutation-based thresholds for genetic mapping (Churchill and Doerge 1994; Carlborg and Andersson 2002), this procedure sidesteps the need to explicitly estimate the effective number of tests.…”
Section: Scan the Genomementioning
confidence: 99%
See 1 more Smart Citation